PENGARUH BELANJA LANGSUNG SEKTOR PENDIDIKAN, KESEHATAN, INFRASTRUKTUR, DAN PERTANIAN TERHADAP IPM (Studi Kasus Pada Kabupaten/Kota Propinsi NTT) - Helda Marlin Ala (Akademi Akuntansi YKPN Yogyakarta, 2015)
This study aims to examine the effect of direct expenditures of education sector, health sector infrastructure and agriculture on the human development index (HDI) is often used as successfulness indicator of the development in a nation or a region. This research is motivated that the direct expenditure of education sector, health sector, infrastructure, and agriculture are important components of the human development index (HDI). The population of this study were the entire area of the district / city in the province of East Nusa Tenggara. The data in this study were secondary data obtained from the Secretariat of the Provincial Finance Bureaue of East Nusa Tenggara and Central Bureau of Statistics of East Nusa Tenggara Province. A total data of 60 observations were used for analysis tool used to test hypotheses is multiple linear regresion. Results of this study show that the direct expenditures of education sector and infrasructure sector have significant positive effects on the human development index. This study, however, does not find evidence that expenditures of health and agriculture sector affect human development index. Keywords : Direct expenditure, education sector expenditure, direct health expenditure, direct infrastructure, direct agriculture, human development index